IMPLEMENTASI SUPERVISI GURU SEKOLAH DASAR SEBAGAI KUNCI PENJAMINAN MUTU PENDIDIKAN - Fitria Sari; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to see how teachers carry out supervision in elementary schools, which is an important tool for ensuring the quality of education. The research was conducted using a qualitative approach and literature study methods through content analysis. The data used in this research comes from books, scientific journals, and various print and online reading sources related to the research topic. Reading and note-taking methods were used to collect data, which was then analyzed descriptively-analytically by discussing concepts and presenting data systematically. Research shows that teacher supervision has a strategic role in improving the quality of learning and professionalism of elementary school teachers. Planning, implementation, evaluation, and structured follow-up are all necessary components for implementing effective supervision. Supervision not only functions as control but also helps teachers become better. This research identifies several key factors for successful supervision, including supervisor competence, open communication, a constructive approach, and commitment from all parties in the supervision process. In conclusion, the implementation of systematic and sustainable elementary teacher supervision is a vital component in the education quality assurance system, which ultimately contributes to improving the quality of learning and overall educational outcomes.